Social media dependency in increasing cancer awareness and screening behaviour among B40 population in Klang Valley: a Facebook cancer support group study - Abdul Halit, Ellysa Nabilah (2025)
Social media has transformed the health communication landscape, offering unprecedented opportunities for disseminating information. However, its effectiveness depends on how users perceive its credibility, usefulness, and their level of dependency on it. With rising cancer mortality in Malaysia, particularly among the B40 population, there is growing concern over low awareness and screening rates in this group. Hence, there is an urgent need to seek an in-depth understanding of the dependency on social media for cancer awareness and screening behaviour among the B40 population in Klang Valley. Grounded by Media Dependency Theory and the Theory of Planned Behaviour, a quantitative survey was conducted with 400 B40 respondents aged 20 and above, selected from Facebook cancer support groups. Descriptive results showed moderate to high levels of social media use and moderate levels of awareness and screening. Spearman's rank correlation revealed significant positive relationships between social media use variables and both cancer awareness and screening behaviour. Factor analysis supported TPB constructs, and Mann-Whitney U tests found a significant gender difference in screening behaviour, with males scoring higher. The findings indicate that social media, when trusted and perceived as useful, can effectively support cancer education and encourage screening, especially in underserved communities. This study highlights the role of social media in public health efforts and the need for tailored digital strategies to reach vulnerable populations like the B40 group.